ANALYSIS OF READING, WRITING, AND COUNTING (CALISTUNG) BASED ON THE LEARNING STYLE OF CLASS II STUDENTS IN MIN 6 PONOROGO: Calistung, Learning Styles, Students - Rodhatul Alawiyah; Hestu Wilujeng; Muammar (El Midad, 2023)
This research is about reading, writing, and counting based on the learning styles of students in class II MIN 6 Ponorogo, this research has the following objectives : 1) analyze calistung based on visual learning stylles, 2) analyze calistung based on auditory learning styles, 3) analyze calistung based on kinesthetic learning styles. This research was conducted using qualitative research methods with descriptive data. Data collection techniques using interviews, documentation, and tests, data analysis techniques use three stages, namely, data reduction, data presentation, and data verification. The coclucions in this study are : 1) students with the most dominant visual learning style with a score of 37 the indicators of calistung, he was able to apply it well and preciesely, 2) students with auditory learning styles with a score of 36, he was able to apply these indicators well, but not maximized. 3) kinesthetic category students with a score of 39, he was only able one of the calistung indicators but the orther indicators were not maximized in their application. Keywords: Calistung, Learning Styles, Students